Selective Synthesis and Thermodynamic Relations of Polymorphic Co(NCS)2‐4‐Dimethylaminopyridine Coordination Compounds. Issue 46 (8th November 2018) - Neumann, Tristan; Jess, Inke; Pielnhofer, Florian; Näther, Christian
Abstract : Reaction of Co(NCS)2 with 4‐dimethylaminopyridine (DMAP) leads to the formation of four new compounds. The crystal structures of Co(NCS)2 (DMAP)2 (H2 O)2 · 2H2 O (1 ), Co(NCS)2 (DMAP)2 (MeOH)2 (2 ) and Co(NCS)2 (DMAP)2 (MeCN)2 (3 ) consist of discrete simple solvato complexes in which the Co cations are octahedrally coordinated by two terminally N‐bonded thiocyanate anions, two DMAP ligands as well as two solvato ligands. Co(NCS)2 (DMAP)2 (4/II ) also forms discrete complexes, but the Co cations are tetrahedral coordinated by two anionic ligands and two DMAP ligands. Upon heating, the hydrate1 transforms into4/II, whereas the methanol solvate2 transforms into a new polymorphic modification of Co(NCS)2 (DMAP)2 (4/I ). For structure determination the corresponding Zn(NCS)2 compound was prepared that is isotypic to4/I . Solvent mediated conversion experiments prove that4 /II represents the thermodynamic stable form at room‐temperature and density functional theory (DFT) calculations indicate that this form is also stable at 0 K. Upon heating both modifications show melting with the higher melting polymorph4/I having the lower melting enthalpy. Temperature dependent X‐ray powder diffraction shows that4/II transforms into4/I upon heating. All experimental results indicate, that both modifications are related by enantiotropism. Abstract : Two polymorphic Co(NCS)2 coordination compounds were synthesized by solvent removal from different precursors, structurally characterized and investigated for their stability, thermodynamic relations and transition behaviour. Both forms are related by enantiotropism and the thermodynamic transition temperature was estimated from their melting enthalpies and confirmed by annealing experiments.